2006
DOI: 10.2337/dc06-0942
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome Is a Risk Indicator of Microvascular and Macrovascular Complications in Diabetes

Abstract: Results from Metascreen, a multicenter diabetes clinic-based survey THE METASCREEN WRITING COMMITTEE* OBJECTIVE -We aimed at assessing the degree of association and the predictive power of the metabolic syndrome with regard to clinically detectable complications in patients with diabetes.RESEARCH DESIGN AND METHODS -Metascreen is a cross-sectional survey of metabolic syndrome and clinically detected diabetes complications performed in 8,497 patients (7,859 with type 2 diabetes and 638 with type 1 diabetes) ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(64 citation statements)
references
References 42 publications
6
58
0
Order By: Relevance
“…This appears to be in accordance with a number of observational studies that suggest that patients who have the metabolic syndrome in concert with type 2 diabetes have a higher frequency of microvascular complications [38,39,40]. In the large Metascreen study conducted in Italy, for example, the metabolic syndrome was independently associated with both macro- and microvascular complications of diabetes [41]. However, not all studies have confirmed this association, a notable exception being the UKPDS [42].…”
Section: Microvascular and Macrovascular Disease Share Similar Risk Fsupporting
confidence: 68%
“…This appears to be in accordance with a number of observational studies that suggest that patients who have the metabolic syndrome in concert with type 2 diabetes have a higher frequency of microvascular complications [38,39,40]. In the large Metascreen study conducted in Italy, for example, the metabolic syndrome was independently associated with both macro- and microvascular complications of diabetes [41]. However, not all studies have confirmed this association, a notable exception being the UKPDS [42].…”
Section: Microvascular and Macrovascular Disease Share Similar Risk Fsupporting
confidence: 68%
“…[27] A number of studies have demonstrated MS to be associated with macrovascular and microvascular complications. [23,28] Cuspidi et al [28] investigated the prevalence of MS in patients with vascular, cardiac and renal organ damage by utilizing the NCEP criteria. They established the prevalence of MS in patients with three-organ damage to be 2.3 times as high as that in patients without organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…The Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR) revealed that the prevalence of any retinopathy was 8% at 3 years and 25% at 5 years. [22] Studies have demonstrated that diabetic patients with MS experienced microvascular complications earlier and more often compared with diabetic patients without MS. [23][24][25][26] Diabetes is known to induce endothelial dysfunction and is a major risk factor leading to microangiopathy. Other MS criteria have also been reported to increase endothelial dysfunction and thus accelerate the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have implicated the metabolic syndrome (MetS) as a potential cause of peripheral neuropathy 11, 12, 13, 14. However, studies that have investigated the contributions of the individual components have revealed mixed results 15, 16, 17, 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 99%